RELATIONSHIP BETWEEN ANXIETY LEVEL IN PANDEMIC AND MEDICAL ADHERENCE IN HYPERTENSIVE ELDERLY - Affandy, Haidar Yusuf (Diponegoro International Medical Journal, 2022)
Abstract Background: Hypertension in Indonesia increases with age. People with hypertension need continuous treatments according to doctor’s recommendation, if not it will cause serious complications. Medication non-adherence of hypertensive elderly caused by many factor, one of them is psychological factor. Health care visits decrease during pandemic because of the COVID-19 transmission anxiety.Objective: To find out the correlation between anxiety level and medical adherence of hypertensive elderly in Kangkung Village, Mranggen during the COVID-19 pandemic.Methods: Cross-sectional study was conducted with Proportional Random Sampling approach on 96 hypertensive elderly in Kangkung, Mranggen, Demak Regency. The study was conducted by interview using Zung Self-rating Anxiety Scale and Morisky Medical Adherence Questionnaire. Data analysis using Rank Spearman correlation test. This study had got Ethical Clearance from Health Research Ethics Committee of Faculty of Medicine of Diponegoro University.Results: There was a correlation between anxiety level and medical adherence, p value = 0,005 (p < 0,01) and the higher anxiety level will decrease the medical adherence (ρ = – 0,287).Conclusion: Anxiety that were experienced by the elderly has been shown to be related to medical adherence during the COVID-19 pandemic.